Comparison of Complications Between Percutaneous Endoscopic Lumbar Discectomy and Open Lumbar Microdiscectomy for The Treatment of Lumbar Disc Herniation (Journal of Rangpur Medical College, 2024)
Background: Lumbar disc herniation (LDH), a common spinal condition causing lower back pain, requires surgical intervention, with common procedures being percutaneous endoscopic lumbar discectomy (PELD) and open lumbar microdiscectomy (OLM). Objective: The study was aimed to compare the complications and outcomes of Percutaneous Endoscopic Lumbar Discectomy (PELD) and Open Lumbar Microdiscectomy (OLM) in treating lumbar disc herniation (LDH) at the L4/L5 level. Methods: A cross-sectional comparative analysis was conducted from January 1, 2022, to June 30, 2023, at the Department of Neurosurgery, National Institute of Neurosciences& Hospital. Seventy patients with LDH were divided into two groups: Group-I (PELD, n=33) and Group-II (OLM, n=37). Baseline characteristics, motor examinations, reflexes, sensory integrity, gait assessments, and MRI findings were recorded. Primary outcomes included per-operative and post-operative complications such as dural tears, nerve root injuries, wound infections, disk space infections, cerebrospinal fluid (CSF) leaks, foot drop, and recurrence rates. Visual Analogue Scale (VAS) scores for lower back and leg pain, and Oswestry Disability Index (ODI) scores, were evaluated pre-operatively and at the 90th postoperative day follow-up. Statistical analysis was performed using the chi-square test in SPSS version 26. Results: Partial nerve root injury occurred in 3.03% of Group-I and 6.06% of Group-II. Post-operative wound infection was noted in 3.03% of Group-I, while no infections were reported in Group-II. CSF leak was observed in 2.7% of Group-II but none in Group-I. Recurrence of LDH occurred in 2.7% of Group-II and none in Group-I. Conclusion: PELD and OLM are both effective for treating LDH, with PELD showing fewer complications.J Rang Med Col. September 2024; Vol. 9, No. 2: 8-14